(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the knowledge and practice of safe intravenous injection among third- and fourth-year medical students at Thai Binh University of Medicine and Pharmacy during the 2024–2025 academic year and to examine factors associated with their knowledge and practice. Method: A cross-sectional descriptive study was conducted on 120 medical students undergoing clinical internships at Thai Binh Provincial General Hospital from September 2024 to April 2025. Data were collected through questionnaires and direct observations based on Ministry of Health guidelines. Results: The study showed that over 70% of students possessed adequate knowledge of SIVI. However, only 62.5% demonstrated adequate practical performance, and glove usage was particularly low at 39.2%. Several factors were found to be significantly associated with safe intravenous injection practices, including knowledge level—students with adequate knowledge were 6.6 times more likely to perform safely compared to those without. Class level, gender, and nationality were also statistically significant factors (p < 0.05). Conclusion: The findings suggest that enhancing students’ knowledge of safe injection practices may positively impact their practical skills. Additionally, greater emphasis should be placed on improving practical competencies, with particular attention to safety measures such as proper glove usage.